(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2024)
Hydnophytum formicarum Jack is an epiphyte also known as “pokok sarang semut” or “pokok kepala beruk”. It is a traditional herbal remedy for hepatitis, rheumatism, diarrhoea, and lung cancer. There is a lack of information about the presence of phytochemicals in this plant, particularly those from Malaysia, and different extraction protocols indicate the presence of different chemicals. For this study, H. formicarum tuber were extracted using hexane, methanol, and ethyl acetate and the chemical compounds were identified using GC-MS. The extracts of H. formicarum tubers yielded 28 different compounds. The tuber of H. formicarum contains a wide range of chemical compounds with potential medicinal values.